Prevalence and determinants of mental distress during COVID-19 outbreak in Bangladesh: evidence from an online survey - Shilpi Rani Saha; Dr. Md. Mobarak Hossain Khan (Yayasan Ahmar Cendekia Indonesia, 2021)
Novel Coronavirus disease 2019 (COVID-19) is an ongoing pandemic and life-threatening highly infectious disease outbreak. The people of Bangladesh are at high risk of COVID-19 and have already experienced various socio-economic, Physical health, and psychological consequences. Particularly, mental health problems are dominantly reported in the literature and should be controlled. The main objective of this epidemiological study is to assess the mental distress and identify its determinants using an online-based survey. Such information is urgently needed to develop feasible strategies for Bangladesh. An online survey was conducted for this study from May 01 to May 05, 2020. A total of 240 respondents provided self-reported online responses. Respondent’s mental distress was measured by the General Health Questionnaire 12 (GHQ-12) and by the self-rated mental health (SRMH) questions. Various kinds of statistical analyses ranging from simple to multivariable logistic recession were performed using SPSS 23.0. About 31.3% and 48.3% of respondents were mentally distressed by GHQ-12 and SRMH questions, respectively. Logistic regression analysis revealed that mental distress was significantly higher among those respondents, whose usual activity was affected by the coronavirus (OR = 6.40, 95% CI: 1.87 - 21.90, p<0.001) and whose financial stress was increased due to lockdown (OR = 2.12, 95% CI: 1.01 – 4.46, p<0.05) on GHQ-12. Female sex (OR = 1.97, 95% CI: 1.03 – 3.75, p<0.05) and respondents with poor mental health before the outbreak (OR = 3.38, 95% CI: 1.18 – 9.72, p<0.05) were also significantly affected by mental distress on SRMH. At least thirty-one percent of the respondents were found to be mentally distressed. Some of the study findings, particularly significant determinants, should be considered while developing strategies to reduce the burden of mental distress among study respondents or similar groups.